(untitled) (Al-Qamar, 2021)
Translation is not limited to the transfer of linguistic vocabulary from the original language to another language. Translation cannot be considered merely a process in which linguistic vocabulary in each language is replaced by similar vocabulary in another language because the exact translation requires importance to the culture of the target language. The translator should investigate the lexical content as well as grammatical structures related to the target language, as well as the different doctrines, value systems and traditions that characterize the pre-translation culture. Translation requires attention to basic cultural elements such as the translators’ knowledge of the customs and traditions of a people’s culture, the verification of the suggestive significance of a product name in a foreign language before it is adopted for the possibility of different meanings of the same language singularity in different languages, careful and careful dealing with comical and comic aspects, The use of grammar, punctuation, and lexicon by influencing the language that we are dealing with, as well as cultural factors such as images, symbols and colors. In the words of the phrase, the competent translator must be fully aware of the culture of the language of origin as well as the target language along with the ability to language aspects. The research’s methodology here is divided between theory and practice. In the first half of the research, the cultural elements that must be considered in the translation process are identified. In the second half, the practical form is mentioned in the Arabic proverbs in Urdu. This article will examine the cultural elements in the process of translation and translation of proverbs to Urdu as a model, and it is divided into a preface and two sub- chapters and conclusion. The introduction addresses the definition of the importance of the translation process and its benefits, and the 1st sub- chapter consists of the most cultural elements, and the second chapter deals with the translation of the Arabic proverbs to Urdu Model, and the conclusion comes with the most important recommendations and proposals.